Monoestolides synthesis from ricinoleic-oleic acids using silicotungstic acid sol-gel catalyst - Mohamad Nordin, Nor Asikin (Penerbit UTHM, 2010)

(untitled)
Sol-gel silica-supported hydrated silicotungstic acid (STA sol-gel), prepared by incorporating hydrated silicotungstic acid (STA) into silica via sol-gel technique, was used as an efficient heterogeneous catalyst for condensation reaction of a mixture ricinoleic acid (RA) and oleic acid (OA). The activity and selectivity of STA solgel for the condensation reaction of a mixture RA and OA have been investigated and compared with unsupported STA and homogeneous perchloric acid. STA solgel and bulk STA catalysts surface were characterized using X-ray Photoelectron Spectroscopy (XPS) analysis. The reactions were carried out under vacuum (2 mBar) for 10 hours at 70 0C under solvent-less conditions. The Liquid Chromatography-Mass Spectrometry (LC-MS) of reaction products results showed chromatographic peaks for the presence of three new monoestolides at retention times (tR) 9.2 min (m/z 577.48, as [M-H]-), 11.2 min (m/z 559.46, [M-H]-) and 12.6 min (m/z 561.48, [M-H]-). STA sol-gel catalyst is new promising heterogenous catalyst that can be used for producing estolide compounds from a mixture of RA and OA. STA sol-gel gave 100 % conversion with 60.62 % selectivity to ricinoleic-ricinoleic monoestolide acid (m/z 577.48, [MH]-), 25.69 % selectivity to ricinoleic-linoleic monoestolide acid (m/z 559.47, [MH]-) and 13.65 % selectivity to ricinoleic-oleic monoestolide (m/z 561.48, [M-H]-).